2015
DOI: 10.1007/s00267-015-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Consolidating the State of Knowledge: A Synoptical Review of Wind Energy’s Wildlife Effects

Abstract: Wind energy development contributes substantially to achieve climate protection goals. Unintended side effects, especially on wildlife, have long been discussed and substantial research has evolved over the last decade. At this stage, it is important to identify what we have learnt so far, as well as which predominant uncertainties and gaps remain. This review article aims to consolidate the state of knowledge, providing a qualitative analysis of the main effects of wind energy development on- and offshore, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 121 publications
2
106
0
6
Order By: Relevance
“…In addition to an extensive field research programme, novel observation methods such as aerial digital survey techniques and bird migration radars were developed. The research of the StUKplus project and the international research obtained similar results regarding the environmental impacts of OWFs (BSH and BMU, 2014;Lüdeke, 2015;Schuster et al, 2015).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…In addition to an extensive field research programme, novel observation methods such as aerial digital survey techniques and bird migration radars were developed. The research of the StUKplus project and the international research obtained similar results regarding the environmental impacts of OWFs (BSH and BMU, 2014;Lüdeke, 2015;Schuster et al, 2015).…”
supporting
confidence: 54%
“…Regarding the impacts of OWFs on benthos (fauna living in, on or nearby the seabed), an increase in their number was observed after OWF construction (Ashley et al, 2014;Coates et al, 2014;Dannheim et al, 2014;Vaissière et al, 2014;Bergman et al, 2015;Schuster et al, 2015;Hammar et al, 2016). However, the species composition changed as a result of the new habitats.…”
mentioning
confidence: 99%
“…Harrison 2011). In addition, there are effects of wind parks -both onshore and offshore -on wildlife (Drewitt and Langston 2006, Mathew 2006, Leung and Yang 2012, Schubert et al 2015). Regarding solar power, possible impairments include glare risks and visual impacts on buildings as well as on landscapes in case of free-standing solar plants (Chiabrando et al 2009).…”
Section: Renewable Energymentioning
confidence: 99%
“…Scientific studies in Europe, as part of preconstruction environmental assessments, and more importantly, dedicated construction and postconstruction research programs, have shed considerable light on the ways in which marine wildlife responds to the construction and operation of offshore wind turbines. These studies have shown that the environmental effects of properly sited, executed, and operated wind projects are, as a general rule, low level (18). For example, fatality rates of birds are lower than might have been anticipated given avoidance behavior (19), and impacts on dolphins and porpoises have been identified as being more of a short-term nature than resulting in long-term consequences (20)(21)(22).…”
Section: Research Requiredmentioning
confidence: 99%
“…An offshore wind project can have a myriad of consequences for wildlife, including displacement, barrier effects, habitat change, disturbance, and fatality (18). Fixed platforms can be used to gain a better understanding of fish, marine mammal, turtle, and seabird movements, decreasing risks through enhanced site selection, and by lowering the cost and shortening the time to investigate individual sites.…”
Section: Research Requiredmentioning
confidence: 99%